Psychometric validation of an empowerment scale for Spanish-speaking patients with rheumatoid arthritis - Contreras-Yáñez, Irazú (Arthritis Res Ther, 2018)
BACKGROUND: Rheumatoid arthritis (RA) knowledge has been constructed with studies performed in Caucasians patients; Latin American patients present unique characteristics. Empowerment is a social multidimensional construct that has been associated to better health-related quality of life in RA. There is no validated instrument for use with Spanish-speaking patients. The objective of the study was to adapt the Spanish version of the Health Empowerment Scale (S-HES), which was selected for its psychometric properties and suitability for low-literacy populations, for RA Hispanic patients (RAEH), and to perform its psychometric validation. METHODS: RAEH adaptation, pilot testing, and psychometric validation were performed. Three convenience samples of RA outpatients from a national tertiary care level center were used. For RAEH adaptation, the word “health” was substituted with “RA” in the original S-HES, integrated by 8 items. Pilot testing (in 50 patients) assessed feasibility. Psychometric validation included content validity (nine experts rated item convenience, clarity, and cultural semantic accuracy), internal consistency (in 200 patients, Cronbach’s alpha) and test–retest (in a subsample of 50 patients, ICC and 95% CI), construct validity (factor analysis), and face validity (in 20 patients, % of agreement). Patients gave written informed consent. RESULTS: Patients were primarily middle-aged females and had typical long-standing disease, although early disease was represented. In the psychometric validation sample, the majority of the outpatients had autoantibodies; meanwhile, half of them had no evidence of disease activity, with acute reactants phase determinations within normal range. Patients with comorbidities and joint replacement were also included. Experts agreed upon the attributes of content validity: 83–100% considered the item was essential, 100% agreed on the item’s clarity and 80–100% on the cultural semantic accuracy. In the pilot sample, ≥ 80% of the patients agreed with the item’s clarity and format. In the psychometric validation sample, mean RAEH was 34 (maximum possible score: 40 = highest score). RAEH had a good internal consistency, Cronbach’s α = 0.86, and moderately good reliability (ICC [95% CI] test–retest: 0.79 [0.62–0.88]). Factor analysis for construct validity showed a single factor explaining 52% of the variance. Patients agreed with each item content validity (85–100%) and clarity (75–100%). CONCLUSIONS: RAEH was valid and reliable to evaluate empowerment in Spanish-speaking RA patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13075-018-1741-6) contains supplementary material, which is available to authorized users.